Fan Identification, Brand Community Identification, and Oppositional Brand Loyalty towards Sponsors of a Rival Sports Team: The Mediating Role of Schadenfreude - David Amani (Journal of Business and Behavioural Entrepreneurship, 2019)
Empirical evidence confirms that brand loyalty is broadly understood in the context of positive side i.e. supportive loyalty compared to negative side i.e. oppositional loyalty. However, theoretically positive (supportive) loyalty cannot be explained exclusively without considering negative (oppositional) loyalty. This study, therefore, examines brand loyalty using a triadic approach combining both negative and positive loyalty in the cycle of love and hate relationship. Specifically, the study examined the influence of fan and brand community identification on oppositional brand loyalty towards sponsors of a rival team in sports industry. A survey cross-sectional research design was adopted, through collecting data using semi-structured questionnaire from 228 highly identified fans of two giant sports teams in Tanzania namely Simba Sports Club and Young Africans Sports Club. The collected data were analyzed using Structural Equation Modelling (SEM), and findings revealed that fan and brand community identification have a strong positive significant influence on oppositional brand loyalty towards sponsors of a rival team when mediated with schadenfreude. Therefore, business firms should take precautions when embarking on sponsorship of highly competing sports teams. Finally, this study adopted a quantitative approach, hence further studies that adopt a qualitative approach is recommended to get a naturalistic picture of subject under the study. Additionally, a comparative study is recommended to compare level of resistance loyalty exhibited by fans of each team.